Problem Solving Oriented Mathematics Curriculum - Anggi Anggara; Mela Aziza (Jurnal Equation: Teori dan Penelitian Pendidikan Matematika, 2020)
Most of students think mathematics as memorising not understanding. They usually use formulas for solving mathematics questions so that when facing non-routine questions they feel frustrating how to solve it. As a mathematics teacher feel dilemma because new curriculum, K13 (curriculum 13) requires them to teach more topic compared than previous curriculum. Consequently, they teach mathematics using textbooks given by government. Due to the limited time to teach many topics, teachers only focus on finishing the topics rather than stimulate students’ problem-solving skills. Therefore, there may be a specific curriculum that can be developed regarding students’ problem solving skills in learning mathematics. Using some literature review, a framework of problem solving oriented mathematics curriculum (PSOMC) was developed. PSMOC has seven principles: Designing, generating, researching, hipotesising, deciding, communicating, and reflecting.